Za pomoc p. Daje najlepszą odp. POMOCY NA JUTRO!!!!!!!!
1.
a) (²/₇)⁻³ * (-²/₇)⁴ =
b) (³/₅)⁻¹¹ * 0,6⁹ * (³/₅)³=
c)13⁷ : 13⁸ =
d) (2¹/₄)⁹ : (2,25)¹⁰ =

2.
a) ((-1,2)²)⁻¹=
b) (((3¹²/₁₇)⁵)⁰)⁻¹¹=
c) (((-2,49)¹)⁻¹)⁻¹
d) ((-¹/₂)²)⁻¹ * (-¹/₂)

3.
a) (⁵/₃)³ * (³/₁₀)³ * (²/₇)³ * (-14)³=
b) (³⁶/₂₅)⁻³ : (4⁴/₅)⁻³=
c) (⁴/₃)⁻² * (0,75)⁻² * (⁵/₆)⁻² * (1,2)⁻²=
d) (-1,2)⁷ : (0,4)⁷ * (¹/₃)⁷=

POMOCY!!!!!!!!!!!!!!!!! OBLICZENIA I ROZWIĄZANIE

1

Odpowiedzi

Najlepsza Odpowiedź!
2010-03-02T13:18:57+01:00
A) (²/₇)⁻³ * (-²/₇)⁴ = (2/7)⁻³*(2/7)⁴ *(-1)=(2/7)⁻³+⁴ *(-1)=(2/7)¹*(-1)=-2/7
b) (³/₅)⁻¹¹ * 0,6⁹ * (³/₅)³=(³/₅)⁻¹¹ * (3/5)⁹ * (³/₅)³=(3/5)⁻¹¹+⁹+³=(3/5)¹=3/5
c)13⁷ : 13⁸ =13⁷ -⁸=13⁻¹=1/13
d) (2¹/₄)⁹ : (2,25)¹⁰ =(2,25)⁹:(2,25)¹⁰=2,25⁹-¹⁰=2,25⁻¹=225/100⁻¹=9/4⁻¹=4/9
2
a) ((-1,2)²)⁻¹=(-1,2)²*⁻¹=(-1,2)⁻²=(-12/10)⁻²=(-6/5)⁻²=(-5/6)²=-25/36
b) (((3¹²/₁₇)⁵)⁰)⁻¹¹=(3¹²/₁₇)⁵*⁰*⁻¹¹=(3¹²/₁₇)⁰=1
c)(((-2,49)¹)⁻¹)⁻¹=(-2,49)¹*⁻¹*⁻¹=(-2,49)¹=-2,49
d)((-¹/₂)²)⁻¹ * (-¹/₂)=(((-¹/₂)²)⁻¹)¹=(-¹/₂)²*⁻¹*¹=(-¹/₂)⁻²=(-2)²=4
3
a)(⁵/₃)³ * (³/₁₀)³ * (²/₇)³ * (-14)³=5/3*3/10*2/7*(-14)=-2
b) (³⁶/₂₅)⁻³ : (4⁴/₅)⁻³=36/25:4 4/5=36/25:24/5=36/25*5/24=6/20
c) (⁴/₃)⁻² * (0,75)⁻² * (⁵/₆)⁻² * (1,2)⁻²=4/3*0,75*5/6*1,2=4/3*3/4*5/6*6/5=1
d) (-1,2)⁷ : (0,4)⁷ * (¹/₃)⁷=-1,2:0,4*1/3=-6/5:2/5*1/3=-6/5*5/2*1/3=-1